Meningkatkan Hasil Belajar melalui Model Pembelajaran Saintifik Kelas VII MTs Darul Mukhlashin Materi Garis dan Sudut - Ainur Selvia; Sholahuddin Al Ayubi; Tri Novita Irawati (Universitas Serang Raya, 2023)
This study aims to improve the learning outcomes of seventh grade students of MTs Darul Mukhlashin in mathematics, especially lines and angles, through the application of the Scientific Learning Model. By involving 16 female students in a qualitative approach and Classroom Action Research (PTK) method, data were collected through interviews, documentation, and tests. The results of the analysis showed that the Scientific Learning Model was very effective; in the pre-cycle, only 4 students achieved the KKM score, but in cycle II, all students managed to meet the KKM. The application of this model makes a positive contribution to the low interest and learning outcomes of students, creating more interesting math learning and understanding the concept of lines and angles. In conclusion, the scientific approach is effective in increasing students' learning ability and improving their perception of mathematics.